RIDDAH DAN KONSEKUENSINYA DALAM HUKUM ISLAM KONTEMPORER - Pipin Suitra (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2018)
The background of the research is based on the author's concern about the rise of apostasy cases that occur in Indonesian society, especially those that occur among public figures in the country. As happened with Lukman Sardi, Asmirandah and others. There has been a pro-contra against this phenomenon, ranging from the phobia of Islam (secular), liberal Islamic groups, radical Islamic groups (Wahhabis), and moderate modernist groups. The crucial point that has become a debate about apostasy is the application of the death law to apostates, which is regulated legally in Islamic law, so that affiliates who reject the total law arise with the pretext of human rights, and groups that defend the law with arguments undeniable. then the writer looks for the midpoint that answers and becomes the solution to this hot issue, by reviewing some classical references (turats), so that a meeting point can be found that can be agreed by both parties. To find the right formula in answering this phenomenon the author uses the Library Research method (library research) by using primary data and secondary data. Data analysis was obtained through library research which was analyzed qualitatively. From this study found answers relevant to apostasy and their consequences in contemporary Islamic law. There are two opinions that seem opposite and contradictory, between the opinions of classical and contemporary scholars. The side of difference is in the legality of beheading for apostates. One group considers it legal with valid arguments while the other group considers it not. Nevertheless there are points of equality in several criteria that justify the execution.